Intruders in a balancing act: Black Economic Empowerment, transitional justice and investment arbitration tribunals - Le Moli, Ginevra (International journal of transitional justice)
This article examines the role of ad hoc investment arbitration tribunals in arbitrating highly sensitive matters in transitional justice contexts, focusing on disputes arising from black economic empowerment (BEE) policies in countries formerly under racially discriminatory regimes. After an overview of the investment protection system, the article introduces the historical context of BEE policies. It subsequently analyses three main disputes, one against South Africa and two against Zimbabwe, where white concession holders and landowners relied on Bilateral Investment Treaties to claim compensation for the consequences of BEE mining and land redistribution policies. These disputes provide a testing ground to shed light on the role of investment arbitration in the context of transitional justice. The article concludes that such a role essentially amounts to an intrusion in the perilous ‘balancing act’ of managing a transitional justice process.